PENGEMBANGAN MEDIA KOMIK MINI DIGITAL PADA MATERI KONSEP KELILING DAN LUAS BANGUN DATAR KELAS IV UNTUK MENINGKATKAN LEVEL BERPIKIR GEOMETRIS VAN HIELE SISWA SEKOLAH DASAR - Meilantiniky Plue, Agustina; Rosalina Bulu, Vera; Williams Fointuna, Daniel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by elementary school students' low understanding of the circumference and area of ​​plane figures, which are still abstract. This study aims to develop a learning medium in the form of a digital mini-comic that is feasible, practical, and effective and capable of improving the Van Hiele level of geometric thinking in fourth-grade elementary school students. The research used a research and development (R&D) model using the ADDIE model. The subjects were fourth-grade students from the UPTD SDI Oesapa Kecil 1 and SDN Kelapa Lima. Data collection techniques were observation, interviews, questionnaires, tests, and documentation. Data were analyzed using quantitative descriptive and inferential analysis with the help of IBM SPSS 27. The results showed that the digital mini-comic media was categorized as very valid, with an average score of 3.81 from material experts, 3.60 from media experts, and 3.44 from language experts. The media was also categorized as very practical based on teacher and student responses in both small-scale and large-scale tests. The results of the small-scale effectiveness test showed a significant difference between the pretest and posttest results of 0.004, with an effect size of 1.236. Meanwhile, the large-scale test showed a significance value of 0.034 with an effect size of 0.697. Furthermore, the digital mini-comic media was able to increase students' geometric thinking levels from the category of not yet reaching the level to Level 0 (visualization) based on Van Hiele's theory. Thus, the digital mini-comic media is suitable for use in mathematics learning on the perimeter and area of ​​plane figures in elementary schools.